2008
DOI: 10.1055/s-2008-1077882
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of Carboxylic Acids and Etherification of Phenols with Amide Acetals

Abstract: The esterification and etherification of unhindered, as well as severely hindered, carboxylic acids and phenols with basic amide acetals, such as N,N-dimethylformamide dimethyl acetal, and their side reactions are discussed. Modified procedures are described in which these side reactions are avoided to achieve high or near quantitative yields of the desired corresponding methyl esters or phenol methyl ethers. On the addition of N,N-dimethylformamide dimethyl acetal, solutions of 4-nitrobenzoic acid in basic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Based on our previous one‐pot cyclization of anthranilic acid and various aminonicotinic acid isomers into quinazolin‐4(3 H )‐ones and pyridopyrimidin‐4(3 H )‐ones, respectively,4 we wished to use amines bearing a propargyl moiety. Microwave irradiation of anthranilic acid ( 1a ) or 2‐aminonicotinic acid ( 2 ) in the presence of N , N ‐dimethylformamide dimethyl acetal (DMFDMA)7 in DMF followed by irradiation with propargylamine in acetic acid gave the expected 3‐(prop‐2‐ynyl)quinazolin‐4(3 H )‐one ( 3 ) and 3‐(prop‐2‐ynyl)pyrido[2,3‐ d ]pyrimidin‐4(3 H )‐one ( 4 ) in excellent overall yields (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous one‐pot cyclization of anthranilic acid and various aminonicotinic acid isomers into quinazolin‐4(3 H )‐ones and pyridopyrimidin‐4(3 H )‐ones, respectively,4 we wished to use amines bearing a propargyl moiety. Microwave irradiation of anthranilic acid ( 1a ) or 2‐aminonicotinic acid ( 2 ) in the presence of N , N ‐dimethylformamide dimethyl acetal (DMFDMA)7 in DMF followed by irradiation with propargylamine in acetic acid gave the expected 3‐(prop‐2‐ynyl)quinazolin‐4(3 H )‐one ( 3 ) and 3‐(prop‐2‐ynyl)pyrido[2,3‐ d ]pyrimidin‐4(3 H )‐one ( 4 ) in excellent overall yields (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that: 'O-alkyl sulphonimidates are unlikely to be synthesized by direct O-substitution. ' We have successfully accomplished the preparation of ethyl N-tert-butyl-4-nitrobenzenesulfonimidate (1) (Equation 1) by silver oxide mediated O-ethylation of Ntert-butyl-4-nitrobenzenesulfonamide (2). The best method we developed is a one-pot procedure involving anhydrous silver(I) oxide, iodoethane, and a sterically hindered sulfonamide, such as 2, in anhydrous, refluxing dichloromethane.…”
Section: Scheme 1 Sulfonimidates From Sulfonimidoyl Chloridesmentioning
confidence: 99%
“…There are a variety of methods for direct alkylation of carboxylic acids at oxygen, but many have limitations because of toxicity, thermal instability, reactivity with moisture in air, multiple components, severe conditions, or extended reaction times. A recent review by Vorbruggen 2 focused on the alkylation of carboxylic acids and phenols with amide acetals. He noted that classical procedures involving sterically hindered tetrahedral intermediates limit the scope of those procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The esterification of carboxylic acids with alcohols is typically achieved under acid catalysis . For more challenging sterically hindered or highly functionalized substrates (namely with acid sensitive functionality), the activation of the acid or the alcohol is often necessary. , An alternative strategy for the synthesis of methyl esters applies diazomethane as the methylating reagent . Under these mild reaction conditions, highly functionalized carboxylic acids are cleanly esterified in excellent yields.…”
mentioning
confidence: 99%